(untitled) (The Journal of Psychology and Sociology, 2013)
Traybolizm of the Kazakh people as ethnic quality which created several centuries. Tribe such as “zhuz” is part of the Kazakh people. Such historical and ethnographic feature as “zhuz” differentiation played a role of preservation of original culture in Kazakh society consciousness. The social traybalizm is a type of participation of certain groups on the basis of genealogical communications which give some social support through existing institutes of mutual aid. It is well known Kazakh people had no police, nursing home, orphanages etc. because so important function of all these «bodies» was carried out by a tribe community. The tribe becomes the major social factor based on feelings of related coherence, represents a certain corporation in which there is a close and regular communication on the basis of the established rituals. The balance of a sort and the nation lies in its basis.